A New Method for Artificial Core Reconstruction of a Fracture-Control Matrix Unit - Qiang Liu; Jianjun Liu; Guihong Pei; Zhengwen Zhu; Yun Lei (Advances in Civil Engineering)
The fracture-control matrix unit (F-CMU) is a special body present in low-permeability fractured reservoirs that can be distinguished by a fracture system and a matrix system. The imbibition phenomenon of the F-CMU provides the possibility for secondary development of low-permeability fractured reservoirs because of the driving force including capillary force and gravity. However, the F-CMU is difficult to obtain during the field core drilling, which has limited the development for laboratory dynamic imbibition tests. Therefore, a new F-CMU reconstruction method is proposed in this study. According to the geometry and parameters, combining laser engraving technology, the fracture system is designed and engraved. Then, the F-CMU is established using a three-dimensional (3D) printed material called polyvinyl alcohol (PVA) as fracture support material which has a faster dissolution rate and causes less damage to the core due to water being the solvent. Finally, the porosity, permeability, and wettability of the matrix system and the T2 spectra from nuclear magnetic resonance (NMR) before and after reconstruction are measured. In addition, numerical simulation calculation of F-CMU permeability is performed. The results show that the characteristic parameters of the matrix system hardly change, indicating low damage to the core. The reconstructed fracture system is found on the T2 spectra, and the fracture permeability is consistent by comparing with the experimental and numerical simulation results. The permeability of the fracture system is about 104 orders of magnitude of the matrix system, which is closer to real core and meets the requirements needed for dynamic permeability experiments.